2018
DOI: 10.1002/ncp.10056
|View full text |Cite
|
Sign up to set email alerts
|

Gastrostomy Tube Feeding in Children With Developmental or Acquired Disorders: A Longitudinal Comparison on Healthcare Provision and Eating Outcomes 4 Years After Gastrostomy

Abstract: This study demonstrates a clear difference between children with developmental or acquired disorders in duration of GT activity and age at GT placement. The study further shows that healthcare provided to children with GT is in some cases multidisciplinary, but primarily focuses on feeding rather than eating.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Patients' primary diagnoses are reported in the NPR using International Classification of Diseases, 10th Revision (ICD-10) codes. 17 Using a categorization established previously, 6,18 the primary diagnoses of children were sorted by the authors as being either 'developmental', for example, neurodevelopmental disabilities or congenital malformations, or 'acquired', that is, relating to conditions contracted after birth (Table S1, online supporting information). In some cases, several diagnostic codes were available, which gave a detailed picture of a child's health and any associated disorders.…”
Section: Study Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients' primary diagnoses are reported in the NPR using International Classification of Diseases, 10th Revision (ICD-10) codes. 17 Using a categorization established previously, 6,18 the primary diagnoses of children were sorted by the authors as being either 'developmental', for example, neurodevelopmental disabilities or congenital malformations, or 'acquired', that is, relating to conditions contracted after birth (Table S1, online supporting information). In some cases, several diagnostic codes were available, which gave a detailed picture of a child's health and any associated disorders.…”
Section: Study Variablesmentioning
confidence: 99%
“…As suggested by Cass, 5 we need to move beyond the overall outcomes of gastrostomy tube insertion to nuance our understanding of alternative feeding methods. In a study exploring the use of gastrostomy tube feeding in 51 children with developmental and acquired disorders, Backman et al 6 found major differences regarding age at gastrostomy tube insertion and eating outcomes after 4 years between the two study groups. Children with developmental disorders (e.g.…”
mentioning
confidence: 99%
“…These time horizons were selected because of the time frame for the dependency of G-tube treatment. 2427…”
Section: Methodsmentioning
confidence: 99%
“…Although the provision of basic nutrition is often in focus, the use of a G-tube also effects feeding, eating and the more culturally charged mealtime, thus covering the biological, psychological and social dimensions of human functioning [2,4]. Previous studies have shown the need for nutrition via a G-tube lasting several years for children with developmental disorders, for example, congenital neurological or chromosomal abnormalities [5,6]. This means that everyday mealtime activities will be deeply affected for a considerable period of time for such children.…”
Section: Introductionmentioning
confidence: 99%
“…Correspondingly, it has been advised that communicative, social and emotional aspects, as well as strategies enabling participation in everyday life, are incorporated into clinical practice, to improve families' mealtimes and increase the overall success of G-tubes [15,19]. Despite the recommendations to address biological, psychological and social aspects in the health care of children using G-tubes, previous research describes a lack of professional guidance to families in adapting to everyday life with a G-tube and a predominant focus on nursing, supporting nutrition, adequate growth and monitoring safe swallowing [5,13,[20][21][22]. Caregivers have expressed frustration towards health professionals as "being removed from the realities of what is going on in the home" [14] (Russel et al 2017, p.7).…”
Section: Introductionmentioning
confidence: 99%